2014
DOI: 10.1007/s10237-014-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach to the computational aeroacoustics of human voice production

Abstract: The aeroacoustic mechanisms in human voice production are complex coupled processes that are still not fully understood. In this article, a hybrid numerical approach to analyzing sound generation in human voice production is presented. First, the fluid flow problem is solved using a parallel finite-volume computational fluid dynamics (CFD) solver on a fine computational mesh covering the larynx. The CFD simulations are run for four geometrical configurations: both with and without false vocal folds, and with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…The velocity is also slightly lower with 2D Smagorinsky and 2D One-Equation compared with [9]. Detailed studies deal with vocal folds are also [11] and [8]. On the Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The velocity is also slightly lower with 2D Smagorinsky and 2D One-Equation compared with [9]. Detailed studies deal with vocal folds are also [11] and [8]. On the Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, unified simulations of phonation and VT acoustics have also been attempted [12,13,14]. However, due to the high computational cost a two step hybrid approach is pursued in those works: the VF movement being obtained from a first FSI simulation, and then prescribed in the computation of the acoustic field.…”
Section: Introductionmentioning
confidence: 99%
“…In a computational study, Sidlof et al [14] have shown that the main aeroacoustic sources are located inside glottis, and in places where the glottal jet interacts with the channel wall. The current study aims at highresolution PIV measurements of the velocity fields in domains, which are crucial for source sound generation.…”
Section: Introductionmentioning
confidence: 99%